Topological characterization of antireflective and hydrophobic rough surfaces: are random process theory and fractal modeling applicable?. (9th January 2015) - Borri, Claudia; Paggi, Marco
Abstract: The random process theory (RPT) has been widely applied to predict the joint probability distribution functions (PDFs) of asperity heights and curvatures of rough surfaces. A check of the predictions of RPT against the actual statistics of numerically generated random fractal surfaces and of real rough surfaces has been only partially undertaken. The present experimental and numerical study provides a deep critical comparison on this matter, providing some insight into the capabilities and limitations in applying RPT and fractal modeling to antireflective and hydrophobic rough surfaces, two important types of textured surfaces. A multi-resolution experimental campaign using a confocal profilometer with different lenses is carried out and a comprehensive software for the statistical description of rough surfaces is developed. It is found that the topology of the analyzed textured surfaces cannot be fully described according to RPT and fractal modeling. The following complexities emerge: ( i ) the presence of cut-offs or bi-fractality in the power-law power-spectral density (PSD) functions; ( ii ) a more pronounced shift of the PSD by changing resolution as compared to what was expected from fractal modeling; ( iii ) inaccuracy of the RPT in describing the joint PDFs of asperity heights and curvatures of textured surfaces; ( iv ) lack of resolution-invariance of joint PDFs of textured surfaces in case of special surface treatments, not accounted for by fractal modeling.